2020
DOI: 10.1088/1757-899x/928/5/052020
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methyl Green Dye from simulated waste water using Hollow Fiber Ultrafiltration Membrane

Abstract: Ultrafiltration has been favorably employed for recycling insoluble dyes and high molecular weight, some type of chemicals and water. Despite, ultrafiltration does not remove low molecular weight and soluble dyes (acid, direct, reactive, basic, etc.). The main advantages of the hollow fiber module are very high packing density and low-energy consumption. In this investigation, the performance of a Polyvinyl chloride (18 wt % PVC) hollow fiber ultrafiltration (UF) membrane for methyl green (MG) dye removal from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, ZnFe 2 O 4 @AC was tested with the leaching study to confirm the heterogeneity of the adsorbent in water. If leaching from the surface of carbon nanocomposites occurs, leached adsorption sites can contribute to the interaction with organic dyes 60 . However, after removing ZnFe 2 O 4 @AC from aqueous solution at 30 min, there was no change in removal efficiency of the dyes (MO, AY, RhB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ZnFe 2 O 4 @AC was tested with the leaching study to confirm the heterogeneity of the adsorbent in water. If leaching from the surface of carbon nanocomposites occurs, leached adsorption sites can contribute to the interaction with organic dyes 60 . However, after removing ZnFe 2 O 4 @AC from aqueous solution at 30 min, there was no change in removal efficiency of the dyes (MO, AY, RhB).…”
Section: Resultsmentioning
confidence: 99%
“…If leaching from the surface of carbon nanocomposites occurs, leached adsorption sites can contribute to the interaction with organic dyes. 60 However, after removing ZnFe 2 O 4 @AC from aqueous solution at 30 min, there was no change in removal efficiency of the dyes (MO, AY, RhB). This result indicated that ZnFe 2 O 4 @AC is not leachable and offers a high stability.…”
Section: Dye Adsorption Isothermsmentioning
confidence: 94%
“…Membrane filtration (MF) technique includes several processes, such as reverse osmosis microfiltration, nanofiltration, and ultrafiltration. But MF processes are suffered from some disadvantages, such as the short-life of the membrane and its high cost [18]. Base on the literature, adsorption technology is widely performed in wastewater treatment because it can eliminate pollutants and discolor dye-water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tremendous amount of study has been dedicated to the expulsion of effluents containing colors with intrinsic toxicity [6]. Adsorption [7], biodegradation by microorganisms [8], coagulation-flocculation [9], electrochemical methods [10], filtration and membrane separation [11][12][13], liquid-liquid extraction [14], ozonation [15], photocatalytic decolorization [16], and wet air oxidation [17] are some of the dye elimination methods that can be used to decrease the environmental impact.…”
Section: Introductionmentioning
confidence: 99%